The Real Option Approach for Strategic Acquisitions: A Case Study of Fubon Acquiring IBA - Huang, Hui Chien (2005)
This dissertation discusses application of real option theory in valuing an strategic acquisition project. Traditionally, discounted cash flow (DCF) models are most commonly used in valuing merger and acquisition projects. However, it is argued that DCF models fail to capture real options that a strategic acquisition project may embed and hence, DCF models are likely to underestimate strategic acquisition cases. By introducing real option theory and option pricing models, it becomes intuitive to use real options analysis to calculate a project's embedded option value. By identifying the real options embedded and incorporating the real options values, the value of an acquisition project can be revealed. This dissertation adopts a case study methodology and demonstrates how real options analysis is used to investigate the value of a target company. The case adopted takes in 2003, when a Taiwanese financial holding company, Fubon, acquires a Hong Kong bank, International Bank of Asia. In conclusion, by appraising the value created by managerial flexibility and future growth opportunities, the importance of incorporating real options value into project value is addressed.